MEASUREMENT OF DISTRIBUTED SITUATION AWARENESS (DSA) FOR OBSERVATION OF REAL-WORLD INSIDE THE PROCESS CONTROL ROOM - SAZALI, MUHAMMAD HAKIMIN (Universiti Teknologi PETRONAS, 2021)
In the process industry, Distributed Situation Awareness (DSA) plays a big role to make sure that plant is safe during abnormal and normal situations